Study the Effect of Annealing on Optical and Electrical Properties of ZnS Thin Film Prepared by CO2 Laser Deposition Technique - Abduljabbar, Layth M. (Iraqi Journal of Laser, 2019)
In this work, ZnS thin films have been deposited by developed laser deposition technique on glass substrates at room temperature. After deposition process, the films were annealed at different temperatures (200ºC , 300 ºC and 400ºC ) using thermal furnace.The developed technique was used to obtain homogeneous thin films of ZnS depending on vaporization of this semiconductor material by continuous CO2 laser with a simple fan to ensure obtaining homogeneous films. ZnS thin films were annealed at temperature 200ºC, 300 ºC and 400ºC for (20) minute in vacuum environment. Optical properties of ZnS thin film such as absorbance, transmittance, reflectance, optical band gap, refractive index extinction coefficient and absorption coefficient have been investigated. From this measurements, the bandgaps energies at room temperature, 200ºC , 300 ºC and 400ºC were found to be 3.7eV, 3.6eV, 3.4eV and 3.3eV respectively. The band gap decreased as the annealing temperature increased. The two point probe method was used for the investigation of electrical properties of the ZnS films such as current voltage characteristics and sheet resistance properties. From these measurements it was found that current decreased as the temperature increased, thus, the annealed films were found to be more resistance than the as-grown films.